2015
DOI: 10.1002/adsc.201500637
|View full text |Cite
|
Sign up to set email alerts
|

Iridium‐Catalyzed [2+2+2] Cycloaddition of α,ω‐Diynes with Cyanamides

Abstract: Thec omplex[ Ir(cod)Cl] 2 /DPPF or rac-BINAP is an efficient catalyst for the [2+ +2+ +2] cycloaddition of a,w-diynesw ith cyanamides.Awide range of cyanamides derived from secondary amines are good coupling partners for a,w-diynes. Ther eaction of unsymmetrical a,w-diynes possessingt wo different internal alkyne moieties with cyanamides is regioselective.Ac ompetitive experiment showed that cyanamide is more reactive than nitrile. This higher reactivity of cyanamide than nitrile was analyzed based on density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 99 publications
1
15
0
Order By: Relevance
“…While PPh3, 2,2'bis(diphenylphosphino)biphenyl (BIPHEP), and DPPF were ineffective at catalyzing the formation of fluorenone 5j (Yield 28% to 63%, entries 2 to 4), excellent yield was realized with the use of 1,2bis[bis(pentafluorophenyl)phosphino]ethane (F-DPPE) (Yield 94%, entry 5). Based on our previous results [45,46,48,49], we envision that the catalytic reaction is initiated by the coordination of diyne 1 to the iridium(I) complex. Oxidative addition of diyne 1 to an iridium(I) complex forms iridacyclopentadiene [51][52][53][54].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…While PPh3, 2,2'bis(diphenylphosphino)biphenyl (BIPHEP), and DPPF were ineffective at catalyzing the formation of fluorenone 5j (Yield 28% to 63%, entries 2 to 4), excellent yield was realized with the use of 1,2bis[bis(pentafluorophenyl)phosphino]ethane (F-DPPE) (Yield 94%, entry 5). Based on our previous results [45,46,48,49], we envision that the catalytic reaction is initiated by the coordination of diyne 1 to the iridium(I) complex. Oxidative addition of diyne 1 to an iridium(I) complex forms iridacyclopentadiene [51][52][53][54].…”
Section: Resultsmentioning
confidence: 98%
“…Sufficient yield was achieved with the use of 1,2-bis(diphenylphosphino)ethane (DPPE) as a ligand to give 83% yield of anthraquinone 3a (entry 3), while other representative bidentate phosphine ligands such as 1,3-bis(diphenylphosphino)propane (DPPP), 1,4-bis(diphenylphosphino)butane (DPPB), and 1,1 -bis(diphenylphosphino)ferrocene (DPPF) were ineffective at achieving a high yield (Yield 22% to 45%, entries 4 to 6). with alkynes, nitriles, and isocyanate to provide a variety of aromatic carbocycles and heterocycles [42][43][44][45][46][47][48][49][50]. In the course of our ongoing investigation into iridium-catalyzed [2 + 2 + 2] cycloaddition, we found that an iridium/bisphosphine catalytic system catalyzed the [2 + 2 + 2] cycloaddition of 1,2bis(propiolyl)benzene derivatives to provide anthraquinones bearing a variety of substituents in an atom-economical manner.…”
Section: Resultsmentioning
confidence: 99%
“…The highest occupied (HO) MO of the iridacyclopentadiene fragment in IIs (Figure 6a) is responsible for the electron delocalization from the iridacyclopentadiene fragment to nitrile. 13 The weight of the C 1 atom in the orbital is 0.223, which is larger than that of the C 4 atom, 0.208, because of the out-of-phase overlap between the Ir atom and the chlorine atom. 30 Not only the σ-donating ability but also the existence of a pπ-orbital of the chloride ligand also affects the difference in reactivity between the two α-carbon atoms (C 1 and C 4 ).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…11 The difference in reactivity between cyanamide and nitrile was also discussed in terms of orbital interactions. 13 Some other groups theoretically determined the mechanism via iridacyclopentadienes for iridium-catalyzed cycloaddition. 16−19 In the present study, we carried out DFT calculations to elucidate the origin of the regioselectivity in the iridiumcatalyzed cycloaddition of a nitrile with an α,ω-unsymmetrical diyne.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Takeuchi and co-workers found [Ir(cod)Cl] 2 /BINAP as an efficient catalyst for the [2 + 2 + 2] cycloaddition of α,ω-diynes 54 with cyanamide nitriles ( Scheme 13 e). The authors argue that the presence of a phosphine-ligand-offered flexibility with respect to the catalytic activity, which could be achieved by choosing the appropriate phosphine ligand [ 27 ].…”
Section: Synthetic Applications Of Substituted Cyanamidesmentioning
confidence: 99%